2018
DOI: 10.1111/jop.12805
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00974 activates TGF‐β/Smad signaling to promote oral fibrogenesis

Abstract: Background Oral submucous fibrosis (OSF) is a progressive scarring disease and has been considered as a premalignant condition of the oral cavity. However, the detailed molecular mechanisms underlying the pathogenesis of OSF are still unclear. Method Here, we examined the expression of a novel long non‐coding RNA LINC00974 in OSF and investigated its function role in myofibroblast transdifferentiation. Phenotypic analyses, including collagen gel contraction, migration, invasion and wound healing assays, were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…In accordance with this finding, the protein expression level of phosphorylated Smad2 was downregulated, as well as myofibroblast marker α-SMA, extracellular cell matrix (ECM) molecules, and type I collagen A1, (Col1a1), following arctigenin administration (Figure 6B). Our recent work has demonstrated that long non-coding RNA LINC00974 activates TGF-β/Smad signaling to promote oral fibrogenesis [19]. We found that the TGF-β production and phosphorylated Smad2 expression were repressed in the LINC00974-inhibited myofibroblasts [19].…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with this finding, the protein expression level of phosphorylated Smad2 was downregulated, as well as myofibroblast marker α-SMA, extracellular cell matrix (ECM) molecules, and type I collagen A1, (Col1a1), following arctigenin administration (Figure 6B). Our recent work has demonstrated that long non-coding RNA LINC00974 activates TGF-β/Smad signaling to promote oral fibrogenesis [19]. We found that the TGF-β production and phosphorylated Smad2 expression were repressed in the LINC00974-inhibited myofibroblasts [19].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, LINC00974 had the opposite effects. LINC00974 was aberrantly upregulated in OSF tissues and myofibroblasts [90].…”
Section: Non-coding Gene Biomarkers In Osf Tissuesmentioning
confidence: 97%
“…Research into lncRNAs has increased in the last 5 years; however, the function of numerous lncRNAs in OSF remains unclear. To date, only four articles have illustrated the relative issues (72)(73)(74)(75).…”
Section: Role Of Lncrnas In Ppoelsmentioning
confidence: 99%
“…Fang et al (74), determined that arecoline-induced myof ibroblast t ra ns-di fferentiation occu r red via LINC00974-mediated activation of the transforming growth factor-β (TGF-β)/Smad signaling pathway. According to their study, collagen gel contractility and myofibroblast migration ability was increased in fibrotic buccal mucosal fibroblasts (fBMFs) overexpressing LINC00974.…”
Section: Role Of Lncrnas In Ppoelsmentioning
confidence: 99%